Bare Nouns in Persian: Interpretation, Grammar, and Prosody - Modarresi, Fereshteh (Université d'Ottawa / University of Ottawa, 2014)
This thesis explores the variable behavior of bare nouns in Persian. Bare singular nouns realize different grammatical functions, including subject, object and indirect object. They receive different interpretations, including generic, definite and existential readings. However, the task of understanding the reasons for, and limits on, this variation cannot be achieved without understanding a number of pivotal features of Persian sentential architecture, including Information Structure, prosody, word order, and the functions of various morphological markers in Persian. After a brief introduction, chapters 2-3 deal with bare noun objects, firstly comparing them with nominals marked with indefinite morpheme -i suffixed to the noun, and the determiner yek. A bare noun object differs from morphologically marked nominals as it shows properties associated with noun incorporation in the literature (chapter 2). Of particular interest are the discourse properties of these ‘quasi-incorporated’ nominals. With respect to the discourse transparency of Incorporated Nominals, Persian belongs to the class of discourse opaque languages within Mithun’s classification (1984). However, under certain circumstances, Persian bare nouns show discourse transparency. These circumstances are examined in chapter 3, and it is proposed that bare nouns do introduce a number neutral discourse referent. There are no overt anaphoric expressions that could match such number-neutral antecedents in Persian. But covert anaphora lack number features, and hence can serve as means to pick up a number-neutral discourse referent. Also, in case world knowledge tells us that the number-neutral discourse referent is anchored to an atomic entity or to a collection, then an overt singular pronoun or an overt plural pronoun might fit the combined linguistic and conceptual requirements, and may be used to pick up the number-neutral discourse referent. This proposal is phrased within Discourse Representation Theory. In the second half of the dissertation, the interpretation of bare nouns in different positions and with different grammatical functions are discussed. Under the independently supported hypothesis of position>interpretation mapping developed by Diesing (1992), we will see the role of the suffix -ra in indicating that an object has been moved out of VP. Following Diesing, I assume that VP-internal variables are subject to an operation of Existential Closure. In many cases, VP-external –ra-marked objects have a different interpretation to their VP-internal, non-ra-marked, counterparts, because of escaping Existential Closure. For subjects, there is no morphological marking corresponding to –ra on objects, and we have to rely on prosody and word order to determine how a VP is interpreted using theories of the interaction of accent and syntactic structure. We assume that VP-internal subjects exist, under two independent but converging assumptions. The first is prosodic in nature: Subjects can be accented without being narrowly focused; theories of Persian prosody predict then that there is a maximal constituent that contains both the subject and the verb as its head. The second is semantic in nature: Bare nouns require an external existential closure operation to be interpreted existentially, and we have to assume existential closure over the VP for our analysis of the interpretation of objects. So, this existential closure would provide the necessary quantificational force for bare noun subjects as well. It is proposed that both subject and object originate within the VP, and can move out to the VP-external domain. The motivation for these movements are informational-structural in nature, relating in particular to the distinctions between given and new information, and default and non-default information structure.
Keywords: Discourse properties of bare nouns; anaphoric reference; Persian Bare Nouns; Topic, focus and interpretation of Bare Nouns; donkey sentences; VP-internal and VP external arguments; bare nouns plurality; number neutral discourse referents; Information Structure; Noun Incorporation; pseduo Incorporation; Quasi-Incorporation; indefinite nouns in Persian; object marker -ra in Persian; Contrastive focus; indefinite markers; Diesing Mapping Hypothesis; Prosody and Bare Noun Interpretation; syntax-prosody mapping; VP-internal objects; VP-internal subjects; -ra a structural marker; Discourse Transparency; Prosody; sentence stress